Agarwood (Aquilaria malaccensis): a review on ecosystem, functions, threats, and potential market in Malaysia - Kamarubahrin, Aimi Fadzirul (SAGE Publications, 2025)
Malaysia is a country rich in biodiversity, particularly in its flora and fauna. Malaysian forests have been exploited for their valuable products since ancient times. One of these high-value products is agarwood (Aquilaria malaccensis), a highly prized commodity used for various purposes such as incense, perfume, traditional medicine, essential oils, and other products in the global market. Although there are several existing reviews on topics related to agarwood, many focus on specific aspects such as its chemical composition, traditional uses, or cultivation techniques. This review aims to provide a holistic and updated perspective on Agarwood, emphasising its ecological functions, threats, and market potential within the Malaysian context. By integrating recent findings and addressing regional nuances, this article seeks to contribute to a more comprehensive understanding of agarwood's multifaceted significance. It draws on literature from abstracts, full-text articles in journals, books, reports, and electronic sources, including Springer, Elsevier, Routledge, Emerald, PubMed, Taylor and Francis, Google Scholar, Web of Science, Scopus, and Science Direct, as well as other relevant websites. Agarwood is a source of numerous economic, social, and environmental benefits that contribute significantly to the well-being of forest-dependent rural communities, regional and national economies, and the achievement of Sustainable Development Goal 15, which focuses on sustainable forest management.